ANALISIS HAPUSNYA HGU BERDASARKAN SURAT KEPUTUSAN PENETAPAN TANAH TERLANTAR DARI BPN : Studi Kasus atas Putusan Nomor : 25/G/2013/PTUN.JKT - Mahruf Mahruf (Jurnal Ilmu dan Budaya, 2017)
Fulfilling the rights of land regulated in the Undang-undang Pokok Agraria (Indonesia’s land law) is meant to enable the holders to make use of the land properly. The unused lands prevailing in cities and villages across Indonesia are considered the act of against the law. Therefore it is imperative that members of the society be informed of their responsibility in this regards, for various economic purposes taking into account the green economy. By doing so the penalty in the form of returning the lands as the property of  the state can be avoided. The paper is a case study of the take-over by the state under the State’s decision   Number : 25/G/2013/PTUN.JKT taking place in Jakarta in 2013.